Supremasi Sistem Peradilan Pidana Anak di Indonesia - Ulum, Miftahul; Hefni, Wildani (Al-Jinayah : Jurnal Hukum Pidana Islam, 2019)
The criminal justice system of Juvenile has not have an obvious regulation yet. It neither formulated the legal criminal action of material. The legal formal in Juvenile Criminal Justice System has been interdependently it doubts the certainty of law as well. It does not have an equal perception of paradigm among the legal officers. The judges just consider the civil law system instead of the substantial justice for juveniles. The juvenile justice system in Indonesia does not yet have a clear legal substance, the juvenile justice law and the juvenile justice system do not formulate clear materials, the statutory law in the juvenile justice process still requires interdependence and obscures the value of legal certainty. There has not been a strong perception and equality of paradigms in the circles of legal freedom (Investigators, Public Prosecutors, Judges, Avocados and Implementers of Criminal Decisions in Children's Prison) in the discussion of correct child law. The lack of infrastructure in the juvenile justice process is also a legal problem. Enforcement of juvenile justice is still shackled by the debate on the civil law system which is more oriented to legal certainty over the value of substantive justice. The justice paradigm is still highlighted in the normative juridical aspects of the sociological juridical. The Integrated Criminal Justice System is not going well. Infra structure of children which is still not feasible. There is no clear philosophical foundation in the juvenile justice process.